2004
DOI: 10.1016/j.jtcvs.2003.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for myasthenic crisis after transsternal thymectomy in patients with myasthenia gravis

Abstract: In this study, postoperative myasthenic crisis after transsternal thymectomy in 122 patients with myasthenia gravis was affected by the existence of preoperative bulbar symptoms, history of preoperative myasthenic crisis, preoperative serum level of anti-acetylcholine receptor antibody > 100 nmol/L, and intraoperative blood loss > 1000 mL. Meticulous preoperative and postoperative care should be carried out to prevent postoperative myasthenic crisis in patients with these prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 28 publications
5
75
0
4
Order By: Relevance
“…58 A multicenter, single-blind, randomized controlled trial is currently investigating the benefit of thymectomy in non-thymomatous MG. 59 Postoperative myasthenic crisis is common after thymectomy; the incidence ranges from 12% to 34%. 60,61 Postoperative crisis in these patients has been related to a history of myasthenic crisis, preoperative presence of bulbar weakness, preoperative serum AChR antibody levels >100 nmol/L, and intraoperative blood loss of >1 L. 61 …”
Section: Thymectomymentioning
confidence: 99%
“…58 A multicenter, single-blind, randomized controlled trial is currently investigating the benefit of thymectomy in non-thymomatous MG. 59 Postoperative myasthenic crisis is common after thymectomy; the incidence ranges from 12% to 34%. 60,61 Postoperative crisis in these patients has been related to a history of myasthenic crisis, preoperative presence of bulbar weakness, preoperative serum AChR antibody levels >100 nmol/L, and intraoperative blood loss of >1 L. 61 …”
Section: Thymectomymentioning
confidence: 99%
“…Co-existing lung disease, Pyridostigmine doses >750 mg/day, a pre-operative forced vital capacity <2.9 L 7 , severe bulbar symptoms and severe myasthenia gravis with previous respiratory crisis and cardiorespiratory disease 8 , a preoperative serum level of anti-acetylcholine receptor antibody >100 nmol/l and intraoperative blood loss >1000 ml were risk factors for postoperative mechanical ventilation 9,10 . Our patient had mild restrictive pulmonary function, a bulbar involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid immunotherapy with plasmapheresis or intravenous immunoglobulin should be performed before thymectomy in patients with preoperative respiratory or bulbar signs. This will help in the postoperative period as well as in reducing preoperatively given corticosteroid levels [44]. Seggia et al [45] showed that plasmapheresis significantly improves respiratory functions and muscle strength in patients with myasthenia treated with thymectomy and significantly reduces hospitalization times.…”
Section: Surgical Methodsmentioning
confidence: 99%